Gene Therapeutic Approaches for the Treatment of Mitochondrial Dysfunction in Parkinson’s Disease - Jannik Prasuhn (MDPI AG, 2021)
Background: Mitochondrial dysfunction has been identified as a pathophysiological hallmark of disease onset and progression in patients with Parkinsonian disorders. Besides the overall emergence of gene therapies in treating these patients, this highly relevant molecular concept has not yet been defined as a target for gene therapeutic approaches. Methods: This narrative review will discuss the experimental evidence suggesting mitochondrial dysfunction as a viable treatment target in patients with monogenic and idiopathic Parkinson’s disease. In addition, we will focus on general treatment strategies and crucial challenges which need to be overcome. Results: Our current understanding of mitochondrial biology in parkinsonian disorders opens up the avenue for viable treatment strategies in Parkinsonian disorders. Insights can be obtained from primary mitochondrial diseases. However, substantial knowledge gaps and unique challenges of mitochondria-targeted gene therapies need to be addressed to provide innovative treatments in the future. Conclusions: Mitochondria-targeted gene therapies are a potential strategy to improve an important primary disease mechanism in Parkinsonian disorders. However, further studies are needed to address the unique design challenges for mitochondria-targeted gene therapies.